A method of screening a banana inducing method provided with LED enhanced light sources - THE INVENTOR HAS WAIVED THE RIGHT TO BE MENTIONED (2017)
A method of screening a banana inducing method provided with LED enhanced light sources is provided. By adopting a single-variable manner, physiological influences of wavelengths of the enhanced light sources on banana tissue culture seedlings are tested through adjustment to determine the optimum wavelengths of the enhanced light sources, a combination of the light sources having different wavelengths is determined according to influences of the light sources having different wavelengths on the banana tissue culture seedlings, and a base culture medium is determined in a manner with the enhanced light sources being unchanged. In addition, the amount of growth of the tissue culture seedlings is introduced and adopted as a screening criterion. The method is more suitable for commercial industrialized production. 本发明提供种具有LED增强光源的香蕉诱导方法的筛选方法，通过使用单变量法调整测试增强光源的波长对香蕉组织培养苗的生理影响，确定最适增强光源波长，并根据不同波长光源对香蕉组培苗的影响，确定不同波长光源出组合，并通过保持增强光源不变方向确定基础培养基，同时引入组培苗的生长量作为筛选标准，更加适合商业工厂化生产。